Oral health and medical conditions among Amish children - Heima, Masahiro (J Clin Exp Dent, 2017)
Background: The Amish are a growing population who live a traditional, rural way of life, which makes them less accepting of modernism. Most Amish live in poverty and are detached from modern health care. In addition, the recent change of their lifestyle has been reported, such as consuming a nontraditional diet and the usage of electronic devices. As a result, their lifestyle change may have impacted their oral health. However, since only a single report about oral health among Amish children has been published approximately three decades ago it has not yet been updated. This study describes oral health among Amish children and their medical conditions during visits to a mobile dental unit (MDU). Material and Methods: The dental records of all patients (N=216) who visited a mobile dental unit were reviewed, which covers 1 year from May 20, 2011, the first date of service. The following factors were taken into consideration during the review process: parental perceptions of their children’s oral health care, dental care experiences, and general health information. Results: Fifty-four (27.8%) children, ages 3 to 17, have never received dental treatment before visiting the MDU; the average number of untreated decayed teeth was 6.8. In spite of this, most parents rated their children’s oral health as good or very good (87.7%). The high cost and long distance travel associated with routine, professional dental care makes it difficult for children to maintain good oral hygiene. Our analysis revealed that bleeding disorders were more prevalent among this gene pool compared to the nation at large; however, asthma was less common. Conclusions: There are oral and general health disparities among Amish children. There is a lack of awareness among Amish parents with regard to their children’s oral health. Key words:Amish, child, dental caries, mobile health units.